Clinical Implication of Pre-operative C-reactive Protein-Albumin Ratio as a Prognostic Factor of Patients With Pancreatic Ductal Adenocarcinoma: A Single-institutional Retrospective Study - MURAKAWA, MASAAKI (In Vivo, 2020)
Background: The C-reactive protein (CRP)-to-serum albumin ratio is associated with a poor prognosis in patients with several cancers. The purpose of this study was to clarify the relationship between the preoperative CRP/Alb ratio and overall survival of pancreatic ductal adenocarcinoma (PDAC) in patients who received radical surgery and S-1 adjuvant chemotherapy. Patients and Methods: We included 117 patients who underwent radical surgery with S-1 adjuvant chemotherapy. We constructed receiver operating characteristic curve (ROC curve) of the CRP/Alb ratio to determine the cut-off value. We analyzed the relationship among the CRP/Alb ratio, clinicopathological status, and survival. Results: The optimal cut-off value of the CRP/Alb ratio was 0.036. All patients were divided into a high-ratio group (CRP/Alb ratio ≥0.036) and low-ratio group (CRP/Alb ratio <0.036). The 5-year overall survival (OS) rates in the high- and low-ratio groups were 22.5% and 36.4%, respectively (p=0.0089). The 5-year disease-free survival (DFS) rates in the high- and low-ratio groups were 12.5% and 22.1%, respectively (p=0.0097). The univariate and multivariate analyses of the OS showed that the pathological N factor and CRP/Alb ratio were independent factors of the survival. The univariate and multivariate analyses of the RFS showed that the pathological N factor, resection margin, and CRP/Alb ratio were independent factors of the survival. Conclusion: The preoperative CRP/Alb ratio is a strong prognostic factor for PDAC patients with undergo curative resection with S-1 adjuvant chemotherapy.